Impact of SARS-CoV-2 on pregnancy and neonatal outcomes: an open prospective study of pregnant women in Brazil - Gomez, Ursula; Francisco, Rossana Pulcineli Vieira; Baptista, Fernanda Spadotto; Gibelli, Maria Augusta B. C.; Ibidi, Silvia Maria; Carvalho, Werther Brunow de; Paganoti, Cristiane de Freitas; Sabino, Ester Cerdeira; Silva, Lea Campos de Oliveira da; Jänisch, Thomas; Mayaud, Philippe; Brizot, Maria de Lourdes (Clinics, 2022)
OBJECTIVES: To determine the incidence and risk of adverse obstetric and neonatal outcomes according to SARS-CoV-2 infection severity in pregnant women. - METHOD: Open prospective study of pregnant women tested for SARS-CoV-2 by serological and molecular assays during pregnancy or delivery in two hospitals in Sao Paulo, Brazil from April 12, 2020, to February 28, 2021. Five groups were considered for analysis: C0, negative COVID-19 results and no COVID-19 symptoms; C1, positive COVID-19 results, and no symptoms; C2, positive COVID-19 results with mild symptoms; C3, positive COVID-19 results with moderate symptoms; and C4, positive COVID-19 results with severe symptoms. The association between obstetric and neonatal outcomes and COVID-19 severity was determined using multivariate analysis. - RESULTS: 734 eligible pregnant women were enrolled as follows: C0 (n = 357), C1 (n = 127), C2 (n = 174), C3 (n = 37), and C4 (n = 39). The following pregnancy and neonatal outcomes were associated with severe COVID-19: oligohydramnios (adjusted Odds Ratio [aOR] = 6.18; 95% CI 1.87‒20.39), fetal distress (aOR = 4.01; 95% Confidence Interval [CI] 1.84‒8.75), preterm birth (aOR = 5.51; 95% CI 1.47‒20.61), longer hospital stay (aOR = 1.66; 95% CI 1.36‒2.02), and admission to the neonatal intensive care unit (aOR = 19.36; 95% CI, 5.86‒63.99). All maternal (n = 6, 15.4%, p < 0.001) and neonatal (n = 5, 12.5%, p < 0.001) deaths and most fetal deaths (n = 4, 9.8%, p < 0.001) occurred in C4 group. Moderate COVID-19 was associated with oligohydramnios (aOR = 6.23; 95% CI 1.93‒20.13) and preterm birth (aOR = 3.60; 95% CI 1.45‒9.27). Mild COVID-19 was associated with oligohydramnios (aOR = 3.77; 95% CI 1.56‒9.07). - CONCLUSION: Adverse pregnancy and neonatal outcomes were associated with maternal symptomatic COVID-19 status, and risk increased with disease severity.
HC-FMUSP-Obstetric COVID-19 Study Group: Aline Scalisse Bassi, Amanda Wictky Fabri, Ana Claudia Rodrigues Lopes Amaral de Souza, Ana Claudia Silva Farche, Ana Maria Kondo Igai, Ana Maria da Silva Sousa Oliveira, Adriana Lippi Waissman, Carlos Eduardo do Nascimento Martins, Danielle Rodrigues Domingues, Fernanda Cristina Ferreira Mikami, Jacqueline Kobayashi Cippiciani, Jessica Gorrao Lopes Albertini, Juliana Ikeda Niigaki, Marco Aurelio Knippel Galleta, Mariana Yumi Miyadahira, Mariana Vieira Barbosa, Mariane de Fatima Yukie Maeda, Monica Fairbanks de Barros, Nilton Hideto Takiuti, Silvio Martinelli, Stela Verzinhas Peres, Tiago Pedromonico Arrym, Veridiana Freire Franco
Gesehen am 02.09.2022